Jennie's Bakeshop, Inc. - Cordero, Rajah B. (School of Management, University of the Philippines Mindanao, 2008)
Jennie's Bakeshop, Inc. is a family-owned business catering to the bakery needs of the town of Mlang and the nearby town of Tulunan. What started to be a home-based bakery has already grown into 5 outlets, a refreshment/fast food and a clubhouse & restaurant. The owner's primary vision of putting up the business is just to have a small source of income to support the growing family. But the also growing market in Mlang was the reason for Mr. Bernie Abasquez, who is the present Vice Mayor of Mlang, and his wife Jennife to expand the bakery and open more outlets. This paper aims to provide Jennie?s Bakeshop with proposed strategies and measures that can help increase its profitability and maximize its potential as a market leader in Mlang and its neighboring towns. Figure 1 is the strategic management model used as a general framework for this paper. Analysis of the strengths, weaknesses, opportunities and challenges/threats showed the following factors as the strongest components that will affect the success of the business. Strengths of Jennie?s are: high record of sales, high capacity of paying financial obligations, the owners strong background in the bakery business and being directly involved in the production and its wide array/ selection of breads. Its weaknesses are: no established Vision, Mission, and Goals, high operating cost and low revenue, no established projection of production; decisions are based on a ?come and go? principle, the lack of new products and the focus on breads and cakes only. For the opportunities, these are: prices are not controlled/regulated by the local agencies, bread as one of the major segments of the food industry and being part of the Filipino diet with per capita consumption of 14kl per year and the Filipino's changing lifestyle of regularly dining with family outside of home. While the threats/challenges are: the increasing prices of flour, other ingredients and packaging materials, generally, bakeries have high operating cost and unstable peace and order situation. Through the use of Quantitative Strategic Planning Model (QSPM), strategies were formulated to address the issues above. The strategies identified are: 1. Produce more/ new products; 2. Expand refreshment menu and add fast food products; 2. Expand market by tapping the canteen in all schools in Mlang. These strategies will maximize the potential and operating assets of Jennie's Bakeshop and increase its sales, which will both, address the minimal revenue it gain with the present production.